Liofairies / Khairul Irfan Khairul Nizam ... [et al.] - Khairul Nizam, Khairul Irfan; Mohd Ali, Alia Nazirah; Radzuan, Syafiqah Syahirah; Borhan, Muhammad Haiqal Hazeeq; Ahmad Subri, Nurul Najihah; Zulkafli, Akhmal Norhisham (2021)
The main purpose of this case study is to analyse the company that we have been selected, which is the Liofairies. It is an online shop that sells two different products which we will elaborate later. As mentioned, Liofairies is an online shop that uses platforms like shopee and also, instagram to promote their products. One of the main findings that is crucial in this case study is the SWOT analysis of the company. This is for us to look for the internal and external causes that can influence the company. From the SWOT analysis, we can identify the advantages that can be taken, minimize risks to the company and also, to find out the weakness and strength which can be addressed accordingly. Other than that, we also discuss the major problems that are faced by the Liofairies. Basically, there are three main problems that we have identified which are time management, online presence and also, competition. So, there are few solutions that we have identified for each of the problems.